Performance of parasitological and molecular techniques for the diagnosis and surveillance of gambiense sleeping sickness. - Dieudonné Mumba Ngoyi; Rosine Ali Ekangu; Marie France Mumvemba Kodi; Patient Pati Pyana; Fatima Balharbi; Mélanie Decq; Victor Kande Betu; Wim Van der Veken; Claude Sese; Joris Menten; Philippe Büscher; Veerle Lejon (Public Library of Science (PLoS), 2014)
OBJECTIVES:Recently, improvements have been made to diagnostics for gambiense sleeping sickness control but their performance remains poorly documented and may depend on specimen processing prior to examination. In a prospective study in the Democratic Republic of the Congo, we compared the diagnostic performance of several parasite detection techniques, immune trypanolysis and of m18S PCR on whole blood stored in a stabilisation buffer or dried on filter paper. METHODS:Individuals with CATT whole blood (WB) titer ≥1∶4 or with clinical signs indicative for sleeping sickness were examined for presence of trypanosomes in lymph node aspirate (LNA) and/or in blood. Blood was examined with Capillary Centrifugation Technique (CTC), mini-Anion Exchange Centrifugation Technique (mAECT) and mAECT on buffy coat (BC). PCR was performed on whole blood (i) stored in guanidine hydrochloride EDTA (GE) stabilisation buffer and (ii) dried on filter paper, and repeatability and reproducibility were assessed. Immune trypanolysis (TL) was performed on plasma. RESULTS:A total of 237 persons were included. Among 143 parasitologically confirmed cases, 85.3% had a CATT-WB titre of ≥1/8, 39.2% were positive in LNA, 47.5% in CTC, 80.4% in mAECT-WB, 90.9% in mAECT-BC, 95.1% in TL and up to 89.5% in PCR on GE-stabilised blood. PCR on GE-stabilised blood showed highest repeatability (87.8%) and inter-laboratory reproducibility (86.9%). Of the 94 non-confirmed suspects, respectively 39.4% and 23.4% were TL or PCR positive. Suboptimal specificity of PCR and TL was also suggested by latent class analysis. CONCLUSION:The combination of LNA examination with mAECT-BC offered excellent diagnostic sensitivity. For PCR, storage of blood in stabilisation buffer is to be preferred over filter paper. TL as well as PCR are useful for remote diagnosis but are not more sensitive than mAECT-BC. For TL and PCR, the specificity, and thus usefulness for management of non-confirmed suspects remain to be determined.